2020
DOI: 10.1186/s42269-019-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between Toxoplasma gondii and type 2 diabetes mellitus: a systematic review and meta-analysis of human case-control studies

Abstract: Objectives: An emerging field of research is examining the association of infectious and environmental pathogens with type 2 diabetes mellitus (T2DM). An understudied pathogen of interest is the protozoan parasite Toxoplasma gondii (T. gondii). The objective of this study was to investigate the possible correlation between T. gondii infection and T2DM. We conducted a systematic review and meta-analysis on the currently available T. gondii seroprevalence data from case-control studies looking at subjects with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recent systematic reviews and meta-analyses [22,33,34] conducted to determine the possible association between T.…”
mentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses [22,33,34] conducted to determine the possible association between T.…”
mentioning
confidence: 99%
“…It was deduced that seroprevalence of anti-T. gondii IgG is higher in T2DM cases than in the controls (P<0.0001). Accordingly, two meta-analysis studies have emphasized a potent association between Toxoplasma exposure and T2DM, but not T1DM [32,33]. The current study aimed to address the involved genotypes of T. gondii in the above groups using the nested-PCR technique and sequencing.…”
Section: Discussionmentioning
confidence: 97%
“…This organism can manipulate the host's immunity and survive the harsh molecular milieu in the body [31]. In addition, Toxoplasma has been speculated to be involved in triggering and or progression of pathophysiological processes of some autoimmune disorders, including DM [26,32,33]. Until now, chronic toxoplasmosis has been significantly correlated to thyroid disease, systemic sclerosis, rheumatoid arthritis, inflammatory bowel syndrome, and hypertension in T2DM patients [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, previous reports have shown that toxoplasmosis develops susceptibility to DM, and diabetic patients are more sensitive to be infected with T. gondii (5,9). This study aimed to evaluate anti-T. gondii IgG antibodies among T1DM patients using ELISA method.…”
Section: Dear Editormentioning
confidence: 97%